Are you thinking too much? Recognition of mental disorders in South African general practice - R.J. Mash (South African Family Practice)
Research shows that up to 24% of primary care consultations have an underlying mental disorder and the majority of these patients are unrecognised in general practice. A number of factors relating to the doctor, patient, health system and research methodology may help to explain this finding. Continuing professional development that targets effective interviewing skills, knowledge of diagnostic categories, therapeutic options and creates awareness of beliefs and attitudes within both the GP and the patient, may be helpful in addressing this issue.